SOSIAL, BUDAYA, DAN EKONOMI BERDASAR PADA PERATURAN BUPATI INDRAMAYU NOMOR 29 TAHUN 2020 TENTANGPEDOMANPEMBATASAN SOSIAL BERSKALA BESAR (PSBB) - Muhammad Asro; Jesy Tasela (Jurnal Kommunity Online, 2021)
AbstractThe background of this research was initiated by a new phenomenon that existed in the community of whole world in the end of 2019 which had been quickly spread to the various parts of the world, and one of them was Indonesia that took part against this virus. Indonesia as a state of law must be present in this problem by making several policies from the central government to the regions in Indonesia. The research aims to obtain an explanation regarding the implementation of large scale of social restriction at the regional level, especially Indramayu Regency through Regent Regulation number 29, 2020 concerning the large scale of social restriction guidelines during the Covid-19 pandemic. The research uses a descriptive analysis method with qualitative approach, the research which by using Case Study Method. The result of the qualitative research is to process descriptive data, for example, conducting interviews and observations as well as supporting references. The results of the research shows some conclusions: (1) The aim of the establishment of the regulation is as a guideline for the implementation of the large sale of social restrictions for handling the Covid-19 in Indramayu Regency, which aims to limit certain activities, due to some principles: juridical, sociological, and philosophical principle in field of social, culture and economy. (2) Regent Regulation Number 29/2020 established on May 4, 2020 by applying administrative sanctions. (3) The evaluation conducted by the special committee concludes that the policies have not been successful yet, but needs to maximize, because spirit and discipline of the community to obey the Regent Regulation is still low and not maximal. It can be seen from the number of cases that always raises. Beside that, socialization and education regarding the Regent Regulation and danger of the Covid-19 have not been maximally conducted by the government to all levels of community.Keywords: regent regulation; covid-19 pandemic; large scale of social restrictionAbstrakLatar belakang penelitian ini diprakarsai oleh adanya fenomena baru yang ada diseluruh masyarakat dunia, pada akhir tahun 2019 yang secara cepat menyebar ke berbagai belahan dunia, salahsatunya Indonesia yang ikut berperang memerangi virus ini. Indonesia sebagai negara hukum, harus hadir dalam permasalahan ini dengan membuat beberapa kebijakan dari pemerintah pusat sampai ke daerah di Indonesia.Tujuan penelitian ini yaitu untuk memperoleh penjelasan mengenai pelaksanaan PSBB pada tingkat  daerah, khususnya Kabupaten Indramayu melalui Peraturan Bupati Nomor 29 Tahun 2020 tentang Pedoman PSBB dalam masa pandemi Covid-19.Penelitian ini menggunakan metode deskriptif analisis dengan menggunakan pendekatan kualitatif. Penelitian dengan metode studi kasus (Case Study). Hasil dari penelitian kualitatif adalah mengolah data yang bersifat deskriptif, misalnya melakukan wawancara dan observasi serta referensi yang mendukung.Hasil penelitian ini mengemukakan beberapa kesimpulan, di antaranya: (1) maksud dibentuknya peraturan tersebut adalah sebagai pedoman pelaksanaan PSBB dalam rangka penanganan Covid-19 di Kabupaten Indramayu, yang bertujuan untuk membatasi kegiatan tertentu, atas pertimbangan beberapa asas di antaranya asas yuridis, sosiologis dan filosofis dalam bidang sosial, budaya dan ekonomi. (2) Perbup No 29/2020 ditetapkan tanggal 04 Mei tahun 2020, dengan menerapkan sanksi administratif. (3) Evaluasi yang dilakukan pansus menyimpulkan bahwa kebijakan tersebut belum berhasil, tetapi terus dimaksimalkan, dikarenakan semangat dan disiplin masyarakat untuk mematuhi perbup tersebut masih kurang dan belum maksimal. Hal ini dapat dilihat dari jumlah kasus yang terus naik. Disamping itu juga, sosialisasi dan edukasi mengenai Perbub dan bahaya Covid-19 belum maksimal yang dilakukan oleh pemerintah kepada seluruh lapisan masyarakat. Kata kunci: strategi pemberdayaan; pendampingan komunitas; kader posyanduDOI-